Responsibility for Criminal Action of Subsidiaries Abused Under the Age due to Heavy Wound (Case Study: Decision Pn. Tangerang No. 71 / Pid-Sus-Anak / 2018 / Pn. Tng) - Angga Bastian; Wasis Susetio (Penerbit Kemala Indonesia, 2021)
This study aimed to describe the cases that had occurred also analyze from the legal side with the applicable law. Here, the name of cases is regarding the abuse carried out by minors which is the result in this case contain a serious injury No: 71/ Pid-Sus-Anak / 2018 / PN Tng. Thus, we proposed a qualitative data study using normative juridical methods. The results showed the process of handling child law prioritizes on diversion process. Here, the legal process in the diversion stage was carried out from the investigation stage, the prosecutor's office, and the court. However, the case relative fail through the trial process at Tangerang district court. Judges in deciding cases use Law regulation no. 11 of 2012 with a sentence of 10 months and training for 3 months. In the court process, there are several things and not appropriate and reduce the child's right to justice where the handling of the child is still not appropriate because the child is detained in a cell not at the Temporary Child Care Institution (LPSA) until the judge's decision read. In detention children are placed in detention (cells) so that this is not in accordance with Law No. 11 of 2012 concerning the juvenile justice system which should place children who conflict with the law placed in the Special Institution for Child Development (LPKA). This case has been done due to the facilities in the Tangerang jurisdiction do not yet have LPSA and LPKA facilities. Thus, for future research it’s expected to give emphasis to the justice of children in conflict with the law in order to get their rights in accordance with Law regulation no. 11 of 2012.